From robots to chatbots: unveiling the dynamics of human-AI interaction - Łukasik, Albert; Gut, Arkadiusz (Frontiers in Psychology, 2025)
The rapid integration of artificial agents—robots, avatars, and chatbots—into human social life necessitates a deeper understanding of human-AI interactions and their impact on social interaction. Artificial agents have become integral across various domains, including healthcare, education, and entertainment, offering enhanced efficiency, personalization, and emotional connectivity. However, their effectiveness in providing successful social interaction is influenced by various factors that impact both their reception and human responses during interaction. The present article explores how different forms of these agents influence processes essential for social interaction, such as attributing mental states and intentions and shaping emotions. The goal of this paper is to analyze the roles that artificial agents can and cannot assume in social environments, the stances humans adopt toward them, and the dynamics of human-artificial agent interactions. Key factors associated with the artificial agent’s design such as physical appearance, adaptability to human behavior, user beliefs and knowledge, transparency of social cues, and the uncanny valley phenomenon have been selected as factors that significant influence social interaction in AI contexts.